Oxazin-5-Ones as a Novel Class of Penicillin Binding Protein Inhibitors: Design, Synthesis and Structure Activity Relationship - Onoabedje, Efeturi Abraham; Ibezim, Akachukwu; Okafor, Sunday Nwankwor; Onoabedje, Ufuoma Shalom; Okoro, Uchechukwu Chris (PLOS ONE, 2016)
Penicillin binding proteins (PBPs) are normal constituents of bacterial which are absent in mammalian cells. The theoretical binding modes of known oxazin-5-ones toward the protein were used as a guide to synthesis new inhibitors. Structural studies of protein-ligand complexes revealed that conformational discrepancies of the derivatives in the protein’s binding site gave rise to the variation in their inhibition constant which ranged from 68.58 μM to 2.04 mM. Biological assay results further confirmed the antibiotic potencies of the studied compounds. Although the outcome of biological screening does not parallel computational predictions, the results obtained from both methods suggest that the oxazin-5-one derivatives are potential PBP inhibitors, hence interesting antibiotic lead agents.